Optimal composition of plaster mortar reinforced with palm fibers - Rachedi Mokhtar (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2018)
The aim of this study is the use of local materials (plaster, sand dunes and date palm fiber) for the region of southern Algeria. By expand areas of the use of these materials in the field of construction. Despite the large ament of gypsum, its use is limited to some secondary operations like coatings and decorative elements. The sand dunes and palm fiber, its use in the construction are very limited. In this study, the sand dunes and palm fiber was added to plaster, to find the mortar that has physical and mechanical properties that allow its use in construction. The results obtained showed that the addition of date palm fibers improves the physical properties (density, water absorption, etc.) and mechanical properties (compression strength, flexural strength, etc).